Regional structural change and the effects of job loss - Melanie Arntz; Boris Ivanov; Laura Pohlan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Routine-intensive occupations have been declining in many countries, but how does this affect individual workers' careers if this decline is particularly severe in their local labor market? This paper uses administrative data from Germany and a matched difference-in-differences approach to show that the individual costs of job loss strongly depend on the task-bias of regional structural change. Workers displaced from routine manual occupations have substantially higher and more persistent employment and wage losses in regions where such occupations decline the most. Regional and occupational mobility partly serve as an adjustment mechanism, but come at high cost as these switches also involve losses in firm wage premia. Non-displaced workers, by contrast, remain largely unaffected by structural change.
Keywords: J24; J63; J64; J65; O33; R11; 330; routine-biased structural change; local labor markets; displacement; mass-layoffs; plant closures; matching; difference-in-differences; event study